2015
DOI: 10.2169/internalmedicine.54.2464
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake is Associated with Renal Involvement in Japanese Patients with Type 2 Diabetes Mellitus

Abstract: Objective The aim of our study was to investigate clinical and nutritional factors associated with renal involvement in patients with type 2 diabetes. Patients We performed a cross-sectional study of 71 patients with type 2 diabetes who were being educated at our hospital from September 2006 to February 2008. The patients were divided into two groups; Group I consisted of 40 patients with both an estimated glomerular filtration rate (eGFR) of ! 60 mL/min/1.73 m 2 and normoalbuminuria, and Group II consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…High-salt intake is recognized as an important global health issue, especially in view of the fact that many commercially available food items often contain more than 100 times higher salt in comparison to homemade food [ 28 30 ]. Epidemiological studies suggest that high-salt intake is associated with an increased risk of multiple sclerosis [ 31 ], chronic kidney disease [ 32 ], diabetes [ 33 ], and chronic heart failure [ 34 ]. Long term clinical intervention studies have not yet been reported but experimental animal models have shown that high-salt can aggravate the severity of EAE by inducing Th17 cells [ 19 , 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-salt intake is recognized as an important global health issue, especially in view of the fact that many commercially available food items often contain more than 100 times higher salt in comparison to homemade food [ 28 30 ]. Epidemiological studies suggest that high-salt intake is associated with an increased risk of multiple sclerosis [ 31 ], chronic kidney disease [ 32 ], diabetes [ 33 ], and chronic heart failure [ 34 ]. Long term clinical intervention studies have not yet been reported but experimental animal models have shown that high-salt can aggravate the severity of EAE by inducing Th17 cells [ 19 , 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 ] The salt restriction improves glomerular hyperfiltration, kidney enlargement, and microalbuminuria in an experimental rat model of diabetes. [ 97 ] Restricting salt and water intake can effectively treat fluid overload in diabetic peritoneal dialysis patients, which may help reduce the use of hypertonic glucose solution. Avoid excessive salt consumption as a preventive measure for avoiding each type of renal calculus formation specially calcium oxalate stones.…”
Section: R Esultsmentioning
confidence: 99%
“…Given this background, it is important to determine the risk factors for developing microalbuminuria and overt proteinuria in patients with diabetes in Japan. We previously analyzed the nutritional factors associated with the onset and progression of diabetic kidney disease (DKD) in a retrospective study of 71 patients with type 2 diabetes 8 . The results showed that obesity, dyslipidemia, hyperuricemia, arteriosclerosis and excessive salt intake were significantly associated with the onset and progression of type 2 diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%